The risks associated with the use of veterinary drugs and chemicals in aquaculture: assessment and control - Rodgers C.J. (The use of veterinary drugs and vaccines in Mediterranean aquaculture, 2009)
The use of antimicrobial agents in aquaculture can lead to both direct and indirect effects, as a result of the response of an organism to the presence of the agent. These effects can be considered in terms of the risks associated with toxicity linked to residues in human food, the development of resistance following antimicrobial therapy or the potential for environmental consequences. There is a current lack of data concerning the conditions required for selection of resistance and the movement of bacteria capable of transferring resistance between specific ecosystem compartments. The contribution of the aquatic-based use of antimicrobial agents and the corresponding non-human use of antimicrobials are compared to use in humans. The quantities of antimicrobial agents used in the agri-food sector and human medicine are not known exactly and there are problems with data standardization and validation. Some risk reduction and control measures are outlined based on the responsible use of antimicrobial agents. It is concluded that the main factors leading to the emergence of antimicrobial resistance relate to the adaptive ability of bacteria, compounded by the use and misuse of antimicrobial agents. The contribution of aquaculture to the global problem of resistance is suggested as minimal.
The Use of Veterinary Drugs and Vaccines in Mediterranean Aquaculture, 2003/05/21-23, Izmir (Turkey)